Stable pediatric kidney transplant recipients run higher urine indoleamine 2, 3 dioxygenase (IDO) levels than healthy children. (1st February 2014) - Khasawneh, Eihab Al; Gupta, Sushil; Tuli, Sanjeev Y.; Shahlaee, Amir H.; Garrett, Timothy J.; Schechtman, Kenneth B.; Dharnidharka, Vikas R
Abstract Immune cells utilize the IDO enzymatic conversion of trp to kyn to determine T‐cell activation vs. anergy/apoptosis. In prior studies, urine IDO levels were higher in rejecting renal allografts than in stable state. However, urine IDO levels in healthy subjects or children are unknown. As a corollary to a larger longitudinal and prospective study of serum and urine IDO levels for transplant immune monitoring, here, we analyzed the difference between urine IDO levels in stable post‐transplant vs. healthy children. IDO levels were measured by tandem mass spectrometry and expressed as kyn/trp ratios. We compared one‐time urine samples, from 34 well children at general pediatric clinics, to the first‐month post‐transplant urine samples from 18 children, while in stable state (no acute rejection or major infection event in next 30 days). Urine kyn/trp ratios were significantly higher in stable children in first‐month post‐kidney transplant (median 16.6, range 3.9–44.0) vs. healthy children (median 9.2, range 3.51–17.0; p = 0.0057 by nonparametric Mann–Whitney test). Higher urine IDO levels even with stable transplant suggest a continuous ongoing low‐grade allorecognition/inflammatory process. Our data also provide baseline urine IDO levels in healthy subjects for use in future studies.